2012
DOI: 10.1016/j.immuni.2012.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of the STING Adaptor Protein Reveals a Hydrophobic Dimer Interface and Mode of Cyclic di-GMP Binding

Abstract: SUMMARY STING is an essential signaling molecule for DNA and cyclic di-GMP (c-di-GMP)-mediated type I interferon (IFN) production via TANK-binding kinase 1 (TBK1) and Interferon regulatory factor 3 (IRF3) pathway. It contains an N-terminal transmembrane region and a cytosolic C-terminal domain (CTD). Here, we describe crystal structures of STING CTD alone and complexed with c-di-GMP in a unique binding mode. The strictly conserved AA153-173 region was shown to be cytosolic and participated in dimerization via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
293
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 297 publications
(310 citation statements)
references
References 53 publications
17
293
0
Order By: Relevance
“…Mutagenesis studies identified key residues involved in binding of c di-GMP. In another recent study, the structure of c di-GMP bound STING (amino acids 139-343) accounted for the observation that dimerization of STING is essential for binding c di-GMP and not only maps the exact location but also provides information on molecular determinants for specificity in binding c di-GMP (Ouyang et al, 2012). This structural information coupled with mutagenesis and cell based studies firmly establishes STING as a bona fide protein that binds c di-GMP in vitro as well as in vivo and elicits IFN production.…”
Section: Role Of Sting In Innate Immune Responsesmentioning
confidence: 99%
See 4 more Smart Citations
“…Mutagenesis studies identified key residues involved in binding of c di-GMP. In another recent study, the structure of c di-GMP bound STING (amino acids 139-343) accounted for the observation that dimerization of STING is essential for binding c di-GMP and not only maps the exact location but also provides information on molecular determinants for specificity in binding c di-GMP (Ouyang et al, 2012). This structural information coupled with mutagenesis and cell based studies firmly establishes STING as a bona fide protein that binds c di-GMP in vitro as well as in vivo and elicits IFN production.…”
Section: Role Of Sting In Innate Immune Responsesmentioning
confidence: 99%
“…4). Whether R231 is involved in binding or facilitating docking unliganded as well as liganded structures of STING (Ouyang et al, 2012). However, what is known and can be observed in the structure is that this loop sits right above the c di-GMP and a mutation of the R231A compromises the ability of STING to respond to c di-GMP, but not DNA.…”
Section: Triggers For C Di-gmp and Nucleic Acid Mediated Activation Omentioning
confidence: 99%
See 3 more Smart Citations